SEMBARANGAN DI KELURAHAN TANGKERANG BARAT KECAMATAN MARPOYAN DAMAI - ", Superman; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Behavior phenomenon housewife littering is now increasingly pay attention and seemed to have become a habit among housewives who want any old young teenagers also participate and perform littering unusual because the old members an example to the younger ones. This study aims to determine why housewives littering and the causes of littering as has happened at this time. Research using qualitative methods with accidental sampling approach. Wenti was collected using questionnaires open the den and formal structured interviews, while the data analysis done by qualitative descriptive analysis. Results revealed Behavior littering the average is married women. Littering behavior is in doing them littering the roadside housewives actually feel concerned on seeing a lot of garbage piled on the roadside but they still hold a sense of habit or laziness do not want discard waste in place. whereas we all might have been equally mengatahui that impact with littering mainly. They or any housewife knows that the garbage that is dirty objects and the kinds of trash that is made up of organic waste and nonargonik. Trash arganik that such rice is rotten, rotten eggs and rotten meat. Impact of waste bins for health is the result of research that respiratory disorders, dengue fever, and skin diseases and so forth, a habit of throwing garbage do housewives so is menggagu activities of others karan with the amount of garbage that piled, iforman has long did throw the behavior of the garbage sembrangan they do bermaca-wide there in the afternoon and some mornings when doing these activities most housewives educated middle and upper schools.Keywords: Behavior, Garbage, Carelessly.